Resistance to amoebic gill disease (AGD) is characterised by the transcriptional dysregulation of immune and cell cycle pathways - Wynne, J; O'Sullivan, MG; Stone, G; Cook, MT; Barbara Nowak; Lovell, DR; Richard Taylor; Elliott, NG (2008)
Amoebic gill disease (AGD) is a parasite-mediated proliferative gill disease capable of affecting a range of teleost hosts. While a moderate heritability for AGD resistance in Atlantic salmon has been reported previously, the mechanisms by which individuals resist the proliferative effects remain poorly understood. To gain more knowledge of this commercially important trait, we compared gill transcriptomes of two groups of Atlantic salmon, one designated putatively resistant, and one designated putatively susceptible to AGD. Utilising a 17k Atlantic salmon cDNA microarray we identified 196 transcripts that were differentially expressed between the two groups. Expression of 11 transcripts were further examined with real-time quantitative RT-PCR (qPCR) in the AGD-resistant and AGD-susceptible animals, as well as non-infected naÃ¯ve fish. Gene expression determined by qPCR was in strong agreement with the microarray analysis. A large number of differentially expressed genes were involved in immune and cell cycle responses. Resistant individuals displayed significantly higher expression of genes involved in adaptive immunity and negative regulation of the cell cycle. In contrast, AGD-susceptible individuals showed higher expression of acute phase proteins and positive regulators of the cell cycle. Combined with the gill histopathology, our results suggest AGD resistance is acquired rather than innately present, and that this resistance is for the most part associated with the dysregulation of immune and cell cycle pathways. Â© 2008 Elsevier Ltd. All rights reserved.